Птицы населенных пунктов Закарпатской низменности - Талпош, В.С. (Вестник зоологии, 1974)
In 1960-1968 more than 100 species of nesting, flying away, wintering and spo radic birds were registered in the settlements of the Transcarpathian lowland. In all the seasons of a year birds density in towns remains high. In April it was 2010, in May- 2226, in August 1892, in October-2188, in December 1900 and in January 1503 individuals per 1 km2 and in villages (May, 1966)-3438 individuals per 1 km2. In January, April, August and October Passer domesticus L. dominated, in May- P. domesticus L., Delichon urbica L. and Streptopelia decaocto Friv., in December -- Passer domesticus L., P. montanus L. In the country-side P. domesticus L., P. monta- nus L., Delichon urbica L. and Hirundo rustica L. dominated in May. Dominating spe- cies in different seasons of a year composed from 64.1 to 82.8% of birds registered on the route.